2009
DOI: 10.1007/s11119-009-9114-4
|View full text |Cite
|
Sign up to set email alerts
|

Laser rangefinder-based measuring of crop biomass under field conditions

Abstract: Knowledge of site-specific crop parameters such as plant height, coverage and biomass density is important for optimising crop management and harvesting processes. Sensors for measuring crop parameters are essential pre-requisites to gather this information. In recent years, laser rangefinder sensors have been adopted in many industrial applications. In agricultural engineering, the potential of laser rangefinders for measuring crop parameters has been little exploited. This paper reports the design and the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
56
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 6 publications
7
56
0
1
Order By: Relevance
“…The solid line of best fit (in relation to the 1:1 line) suggests that the combined sensor index tended to underestimate the actual GDM and this is consistent with the observations of other workers. It has been reported that the morphology of the vegetation canopy greatly influences the accuracy of some laser rangefinders [33]. In particular, vegetation with an erectophile morphology (typical in grasslands and pastures) produce higher uncertainties in height measurements and tends to underestimate the mean reflection height [33,34], due to the outgoing laser beam typically glancing off the erectophile vegetation rather than reflecting back towards the sensor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid line of best fit (in relation to the 1:1 line) suggests that the combined sensor index tended to underestimate the actual GDM and this is consistent with the observations of other workers. It has been reported that the morphology of the vegetation canopy greatly influences the accuracy of some laser rangefinders [33]. In particular, vegetation with an erectophile morphology (typical in grasslands and pastures) produce higher uncertainties in height measurements and tends to underestimate the mean reflection height [33,34], due to the outgoing laser beam typically glancing off the erectophile vegetation rather than reflecting back towards the sensor.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the morphology of the vegetation canopy greatly influences the accuracy of some laser rangefinders [33]. In particular, vegetation with an erectophile morphology (typical in grasslands and pastures) produce higher uncertainties in height measurements and tends to underestimate the mean reflection height [33,34], due to the outgoing laser beam typically glancing off the erectophile vegetation rather than reflecting back towards the sensor. For this study, the NDVI was the only SRI that was examined as a predictor of biomass, the reason for this being that is it a commonly used index as well as the fact that NDVI is one of the standard outputs from the Raptor™ sensor.…”
Section: Resultsmentioning
confidence: 99%
“…dust, vibration, and sun. Ehlert et al, 2009 have generally shown that laser scanners are able to meet these requirements. However, tractorbased systems are bound to the tramlines to measure the plant height.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, studies show that terrestrial laser scanning (TLS), as an active system, can be applied for agricultural purposes. Investigated plant parameters are plant height (Zhang and Grift, 2012), biomass (Keightley and Bawden, 2010;Ehlert et al, 2009;2008), crop density (Hosoi and Omasa, * Corresponding author: nora.tilly@uni-koeln.de 2012;Saeys et al, 2009), and leaf area index (Gebbers et al, 2011). As mentioned the large height of maize plants causes difficulties for ground based system.…”
Section: Introductionmentioning
confidence: 99%